Assessment of the quality of research and practice events using telemedicine technologies at the National Medical Research Center for Therapy and Preventive Medicine during the COVID-19 pandemic - O. M. Drapkina; R. N. Shepel; S. Yu. Astanina; T. V. Vakhovskaya; T. V. Sapronova; T. V. Samoilov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the quality of research and practice (RP) events using telemedicine technologies (TMT) at the National Medical Research Center for Therapy and Preventive Medicine, implemented in 2021 during the coronavirus disease 2019 (COVID-19) pandemic.Material and methods. At the end of RP events using TMT in 2021, the observers were asked to fill out the checklist “Quality of RP events using TMT” in a digital survey form no later than 3 days from the date of the event. The questionnaire consisted of 19 questions on the content and organizational part of the event, each of which was asked to answer “yes” or “no”. Further, cluster analysis of the responses received was performed with subsequent scoring according to the cluster rank. For each positive answer, points were awarded according to the proper cluster (range): 1 point (bad) — proportion of “yes” is from 0 to 20%; 2 points — from 20 to 40%; 3 points (satisfactory) — from 40 to 60%; 4 points (good) — from 60 to 80%; 5 points (excellent) — >80%. To evaluate the final result of events’ quality, based on the developed integrated approach, a scale was used where the total score of 90 or more corresponds to an excellent rating, 8589 — good, 80-84 — satisfactory, less than 80 — bad. Statistical analysis, accumulation, adjustment, systematization of initial data and visualization of the obtained results were carried out in Microsoft Office Excel 2021 spreadsheet software.Results. In total, in 2021, 157 RP events were implemented using TMT, in which 24277 individual and group connections were recorded, as a result of which 3359 checklists were fully completed. The analysis of obtained answers showed the total score of 92, which corresponds to an excellent rating.Conclusion. The assessment of the quality of RP events using TMT at the National Medical Research Center for Therapy and Preventive Medicine, implemented in 2021 in the context of a COVID-19 pandemic, showed that the these activities have an excellent quality rating. At the same time, the totality of RP events can be considered as an integral system, and its quality should be considered as the correspondence of events’ organization and content to the expected needs of trained doctors.